The Government’s disregard for evidence is an own goal - Stevens, Craig (New Zealand Science Review, 2016)
​ The New Zealand Association of Scientists (NZAS) is alarmed at the Government’s response to a recent study by Motu researchers, and asks John Key to consider the implications of undermining his Government’s own big data initiative for short-term political gain. The Government has invested millions of dollars to construct a database that tracks the performance of every business and every employee in New Zealand’, said the NZAS President Craig Stevens, ‘but for New Zealanders to benefit from this investment, the Prime Minister needs to be prepared to listen to what the data says.’90-day employment trials were introduced for all businesses after a pilot suggested that the trial periods ‘encouraged employers to take on new staff and helped those at the margins of the labour market, particularly young people, get jobs’. Using the Government’s database, Motu researchers Dr Isabelle Sin and Nathan Chappell were able to measure the impact of the trials on employment. They found that it was very unlikely that either of these objectives had been achieved.’ By dismissing the results of Motu’s study as ‘academic’ and resorting to anecdote to justify the policy instead, said Stevens, ‘the Prime Minister undermines his Government’s stewardship of New Zealanders’ private data.’ The Association calls on the Government to make responsible use of big data, and this includes ensuring that the evidence it provides is taken seriously, regardless of whether that evidence is politically palatable. Stevens said ‘as a society and an economy we face challenges from many sides, to dismiss careful research is not helpful’.